2008
DOI: 10.48550/arxiv.0806.0901
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tridiagonal pairs and the q-tetrahedron algebra

Abstract: The q-tetrahedron algebra ⊠ q was recently introduced and has been studied in connection with tridiagonal pairs. In this paper we further develop this connection. Let K denote an algebraically closed field and let q denote a nonzero scalar in K that is not a root of unity. Let V denote a vector space over K with finite positive dimension and let A, A * denote a tridiagonal pair on V . Let) denote a standard ordering of the eigenvalues of A (resp. A * ). T. Ito and P. Terwilliger have shown that when θ i = q 2i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Some notable papers on the topic are [6, 13, 28-31, 35-37, 71]. There are connections to representation theory [2,9,21,26,29,31,39,41,42,64,65,75], partially ordered sets [73], the bispectral problem [5,6,[22][23][24]82], statistical mechanical models [8-14, 17-20, 62], and other areas of physics [61,81,83].…”
Section: Tridiagonal Pairsmentioning
confidence: 99%
“…Some notable papers on the topic are [6, 13, 28-31, 35-37, 71]. There are connections to representation theory [2,9,21,26,29,31,39,41,42,64,65,75], partially ordered sets [73], the bispectral problem [5,6,[22][23][24]82], statistical mechanical models [8-14, 17-20, 62], and other areas of physics [61,81,83].…”
Section: Tridiagonal Pairsmentioning
confidence: 99%
“…We refer the reader to [1,2,[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] and the references therein for background information on TD pairs.…”
Section: Tridiagonal Pairsmentioning
confidence: 99%
“…It is an open problem to classify the sharp TD pairs up to isomorphism, but progress is being made [4,8,11,12,14,16,18]. Concerning the nonsharp TD pairs, relatively little research has been done.…”
Section: Tridiagonal Pairsmentioning
confidence: 99%
“…Over time, connections were found between TD pairs and other areas of mathematics and physics. For instance, there are connections between TD pairs and representation theory [1,6,12,14,16,19,20,33], orthogonal polynomials [28,32], partially ordered sets [29], statistical mechanical models [2,5,27], and other areas of physics [21,26]. Among the above papers on representation theory, there are several works that connect TD pairs to quantum groups [1,6,12,16].…”
Section: Introductionmentioning
confidence: 99%
“…They showed that these TD pairs induce a U q ( sl 2 )-module structure on their underlying vector space. In [6], Funk-Neubauer extended this construction to TD pairs of q-Hahn type. In [12], Ito and Terwilliger extended the construction to the entire q-Serre class.…”
Section: Introductionmentioning
confidence: 99%